Bioengineering case studies : sustainable stream bank and slope stabilization - Goldsmith, Wendi (Springer New York, 2014)
This unique volume describes and evaluates 30 projects from across the United States where bio-stabilization was employed to address a detrimental naturally occurring process or byproduct of the built environment. Bio-stabilization (or soil bioengineering) refers to the use of plant materials, primarily live cuttings, arranged in the ground in different arrays to reinforce soils and protect upland slopes and/or stream banks against surficial erosion and shallow slope failures. Examples included in the collection represent different regions of the country and their specific conditions and challenges. Each project is illustrated with a number of distinctive photographs to support the reader's understanding and showcase the wide scope of projects and techniques presented. This book also: ·         Presents a range of well-documented case studies on key techniques and best practices for bio-stabilization projects ·         Emphasizes evaluation and comparison of different techniques and challenges across a wide range of project types and geographies ·         Adopts a clear and consistent descriptive scheme and performance evaluation rubrics for 35 bio-stabilization projects, including efforts protecting/repairing watersheds, stabilizing slopes along highways, and protecting stream banks and coastal slopes ·         Offers abundant visual detail, featuring four to five high-quality photographs for each project, totaling nearly 150 images Bioengineering Case Studies is an ideal book for civil and environmental engineers and environmental scientists working on watershed, infrastructure projects, and municipal scale installations.